The rise of online banks in Italy “WIDIBA Bank” Case Study - Alessio Faccia; Narcisa Roxana Moşteanu; Luigi Pio Leonardo Cavaliere; Gabriele De Santis (Financial Markets, Institutions and Risks)
The digitalization of technologies for the functioning of the country’s economy, in particular banking institutions, has made a significant impetus to accelerate their development. It is stated that the use of advanced information technologies in the banking sector of the economy (which was gradually formalized into the concept of “online banking”) has greatly facilitated the implementation of financial transactions, in particular, minimized the physical circulation of money. The purpose of the article is to study the features and principles of online banking on the example of the Italian bank WIDIBA. Methodical support of the paper includes a method of analysis of specific situations. The key components of the case method of the study are: research on the basis of literature review; formalization of key theses (issues) in the context of the unresolved part of the study; accumulation and analysis of collected information; identification of key features of the issue. This research was carried out in the light of two aspects: the strategic principles of the spread of online banking in Italy; digital technologies in the context of the strategic perspective of the Italian bank WIDIBA. The paper considers the historical aspects of the introduction and use of online banking services. It is noted that in Italy today there are 207 publicly registered commercial establishments, of which 81 are located abroad, and 6 operate mostly in the format of providing online banking services. The object of this research is the activity of the Italian bank WIDIBA, which is justified by its valuable practical experience in formalizing a plan of adequate timely strategy for entering the market of online banking services on the basis of a carefully developed development strategy. The theoretical researches were carried out in the work, in particular, in the following directions: definition of strategic actions of bank establishment according to a time lag of functioning; analysis of the budget of the banking institution (net profitability, interest margin, operating and administrative expenses, etc.); analysis of the income statement of the bank (the ratio of net profit and loss, interest margin and brokerage margin); work with financial report or balance sheet data on the structure of assets, liabilities and investments, retained earnings; study of trend dynamics of cash flows (operational, financial, investment and free cash flows). Excellent strategies are analyzed, which demonstrate how the banking sector is extremely dynamic and, that technological investments still allow easier access to new operators in case of the implementation of innovation strategies.